2005
DOI: 10.1074/jbc.m408679200
|View full text |Cite|
|
Sign up to set email alerts
|

Brn-3a Transcription Factor Blocks p53-mediated Activation of Proapoptotic Target Genes Noxa and Bax in Vitro and in Vivo to Determine Cell Fate

Abstract: The Brn-3a POU transcription factor is associated with survival and the differentiation of sensory neuronal cells during development. Brn-3a mediates its effects either by the direct regulation of target genes or indirectly upon interaction with proteins such as p53. Brn-3a differentially regulates p53-mediated gene expression and modifies its effect on cell fate. Here we show that, like Bax, Brn-3a antagonizes p53-mediated transcription of another proapoptotic target, Noxa, significantly reducing transactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 34 publications
2
59
0
Order By: Relevance
“…20,21 However, since the expression pattern and neuronal phenotype of the Brn-3a KO are paralleled by neuronal loss seen in p73 KO, we believe that this interaction may be more physiologically relevant in specific neurons. At a functional level, similar to the effects seen with p53, Brn-3a alters p73 target gene expression in a complex manner: it antagonizes TAp73a and p73b activity on the bax promoter but co-operates with these isoforms to enhance p21 CIP1/Waf1 .…”
Section: Actinmentioning
confidence: 99%
See 3 more Smart Citations
“…20,21 However, since the expression pattern and neuronal phenotype of the Brn-3a KO are paralleled by neuronal loss seen in p73 KO, we believe that this interaction may be more physiologically relevant in specific neurons. At a functional level, similar to the effects seen with p53, Brn-3a alters p73 target gene expression in a complex manner: it antagonizes TAp73a and p73b activity on the bax promoter but co-operates with these isoforms to enhance p21 CIP1/Waf1 .…”
Section: Actinmentioning
confidence: 99%
“…Brn-3aÀ/À mutants suffer significant loss of sensory neurons by apoptosis during development, and this correlated with elevated Bax expression. 20 These neurons are rescued during embryogenesis by the loss of bax as demonstrated in Brn-3a/Bax double KO. 3,4 Thus, the ability of Brn-3a to antagonize transactivation of Bax by p73 is likely to play an important role in neuronal survival during development.…”
Section: Actinmentioning
confidence: 99%
See 2 more Smart Citations
“…Noxa is a BH3-only member of Bcl-2 family proteins and its expression is induced by DNA damage such as that caused by etoposide or doxorubicin in a p53-dependent manner Shibue et al, 2003). Furthermore, several lines of evidence reported that Noxa is one of the most important cell death effectors in neuronal cell death, for example, nuclear factor-kappa B modulated cell death in mouse cortical neurons (Aleyasin et al, 2004), axotomized motor neurons of adult mouse (Kiryu-Seo et al, 2005), sensory neurons especially in trigeminal ganglia and cervical dorsal ganglia (Hudson et al, 2005) and arsenite-induced cortical neurons (Wong et al, 2005).…”
Section: Introductionmentioning
confidence: 99%